2014
DOI: 10.1587/transinf.e97.d.1567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Voluntary Movements on Audio-Tactile Temporal Order Judgment

Abstract: SUMMARYThe present study aims to investigate the effect of voluntary movements on human temporal perception in multisensory integration. We therefore performed temporal order judgment (TOJ) tasks in audio-tactile integration under three conditions: no movement, involuntary movement, and voluntary movement. It is known that the point of subjective simultaneity (PSS) under the no movement condition, that is, normal TOJ tasks, appears when a tactile stimulus is presented before an auditory stimulus. Our experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 27 publications
(32 reference statements)
4
23
2
Order By: Relevance
“…This direction of bias in PSS has been reported repeatedly for passive audiotactile TOJ (Zampini et al, 2005; Nishi et al, 2014; Hao et al, 2015), suggesting that the tactile event should be presented slightly earlier than the auditory one for it to be perceived simultaneously with the auditory event. We observed no significant differences of PSSs between the conditions.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This direction of bias in PSS has been reported repeatedly for passive audiotactile TOJ (Zampini et al, 2005; Nishi et al, 2014; Hao et al, 2015), suggesting that the tactile event should be presented slightly earlier than the auditory one for it to be perceived simultaneously with the auditory event. We observed no significant differences of PSSs between the conditions.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have examined the effects of voluntary movements on temporal perception of sensory events without causal relationship between voluntary movements and sensory events (Frissen et al, 2012; Nishi et al, 2014; Hao et al, 2015). In contrast, the present study examined whether voluntary movements improve perceptual sensitivity to temporal disparity between mutltisensory events when those events are virtually caused by the voluntary movements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a TOJ task, the participants are required to judge the temporal order of the two stimuli. These tasks have revealed that people tend to perceive different modal stimuli as occurring simultaneously when they are presented with a short lag ( Slutsky and Recanzone, 2001 ; Lewald and Guski, 2003 ; Kayser et al, 2008 ; Shi et al, 2008 ; Nishi et al, 2014 ). More specifically, the PSS differs from the point of physical simultaneity.…”
Section: Introductionmentioning
confidence: 99%